Media and power: a critical discourse analysis of Habib Rizieq's coverage in Indonesian mainstream media - Sahide, Ahmad; Misran, Misran (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
The aims of this article is to see the Indonesian media framing toward Habib Rizieq after returning to Indonesia, from Saudi Arabia in 2020. Habib Rizieq Shihab has become one of the media's figures since returning from Saudi Arabia in November 2020. Habib Rizieq is one of the foremost religious figures who has fought or delegitimized Joko Widodo's leadership since 2014. Habib Rizieq has fought for the enforcement of Islamic law in Indonesia and against Jokowi's regime, which he sees as less pro-Islam. The theory used in this article is framing theory.This article analyzes the mainstream media's framing in Indonesia, namely Kompas, Tempo, Jakarta Post, and Republika, in reporting on Habib Rizieq Shihab's figure. In this study, we processed data using the Nvivo 12 and VOSviewer application tools to see media sentiment. In this research, we read 317 news from the four mainstream medias in Indonesia from October to December 2020. We use four keywords in the framing analysis: positive, negative, moderately positive, and moderately negative. This study indicates that moderately negative framing is the highest in Indonesia's mainstream media coverage on Habib Rizieq Shihab's figure. It means that Habib Rizieq failed to reconstruct the power of the masses against Joko Widodo’s regime.